Sleep Quality and Levodopa Intestinal Gel Infusion in Parkinson’s Disease: A Pilot Study - Oriol De Fabregues; Alex Ferré; Odile Romero; Manuel Quintana; José Álvarez-Sabin (Parkinson's Disease)
Background. Sleep problems in patients with advanced Parkinson’s disease (PD) have a deleterious impact on quality of life. Objective. To assess the effect of levodopa-carbidopa intestinal gel (LCIG) infusion on sleep quality in advanced PD patients. Methods. Seven patients participated in a prospective pilot study. Before and after 6 months of LCIG infusion, an overnight polysomnography was performed and the Epworth Sleepiness Scale, fatigue scale, Pittsburgh Sleep Quality Index, Beck Depression Inventory, and the Hamilton Anxiety Rating Scale were administered. Results. PSG showed low sleep efficiency. REM sleep without atony was found in 5 patients. After 6 months of LCIG infusion, the percentage of REM sleep decreased as well as the number of arousals especially due to reduction of spontaneous arousals and periodic leg movements during REM sleep, but differences were not statistically significant. Also, scores of all study questionnaires showed a tendency to improve. Conclusion. The results show a trend toward an improvement of sleep quality after 6 months of LCIG infusion, although differences as compared to pretreatment values were not statistically significant. The sleep architecture was not modified by LCIG. Further studies with larger study samples are needed to confirm these preliminary findings.